2019
DOI: 10.3390/coatings9030163
|View full text |Cite
|
Sign up to set email alerts
|

Thermochromic Behavior of VO2/Polymer Nanocomposites for Energy Saving Coatings

Abstract: Vanadium dioxide (VO2) is a well-known thermochromic material that can potentially be used as a smart coating on glazing systems in order to regulate the internal temperature of buildings. Most growth techniques for VO2 demand high temperatures (>250 °C), making it impossible to comply with flexible (polymeric) substrates. To overcome this problem, hydrothermally synthesized VO2 particles may be dispersed in an appropriate matrix, leading to a thermochromic coating that can be applied on a substrate at a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 43 publications
(86 reference statements)
1
13
0
Order By: Relevance
“…As a result, we chose two polymersPVA and PVP-K30to prepare VO 2 /PVA and VO 2 /PVP composite films as they improved NP dispersion by maintaining/enhancing the optical performance of VO 2 and fulfill the temperature requirement. The ratio between VO 2 /polymers plays a significant role in the thermochromic properties of the composite thin films . As shown in Figure , it is only with an optimum VO 2 /polymer ratio high-quality thermochromic thin films can be achieved.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, we chose two polymersPVA and PVP-K30to prepare VO 2 /PVA and VO 2 /PVP composite films as they improved NP dispersion by maintaining/enhancing the optical performance of VO 2 and fulfill the temperature requirement. The ratio between VO 2 /polymers plays a significant role in the thermochromic properties of the composite thin films . As shown in Figure , it is only with an optimum VO 2 /polymer ratio high-quality thermochromic thin films can be achieved.…”
Section: Resultsmentioning
confidence: 99%
“…However, due to the multivalent nature of the vanadium ions, VO 2 is highly oxygen or air sensitive and is oxidized into other polymorphs of VO x with severely deteriorated thermochromic performances upon air exposure. , The stability and uniformity while retaining or enhancing the desired functionality of VO 2 thin films prepared from solution-based processes are crucial factors for practical applications. Forming composites with polymers represent one important strategy in improving the uniformity and stability of oxide NP-based films. , Recent studies have demonstrated VO 2 /polymer composite films prepared using crystalline VO 2 NPs. However, most of these processes involve limited scalability and complex processing, which are not favorable for large-scale applications. In addition, the films have offered inadequate IR modulation , and experienced a dramatic drop of luminous transmittance when heated . Further, the widely used spray-coating method typically requires delicate formulations of inks (such as solvent, concentration, and composition) and frequently results in non-uniform films, whereas spin coating is limited to prepare small-area thin films. , It is thus of great significance to explore facile and scalable solution-based strategies to achieve uniform and stable VO 2 -based thermochromic thin films to facilitate their practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The expression above is obtained by identifying the critical transition temperature through heating (T t max ), 68 °C, and cooling temperature (T t min ), 62 °C. As such, we can calculate W, the width of the transition, and include information about the temperature width of the IMT transitions for VO 2 nanofilm, which is calculated by [16,21] and given as.…”
Section: The Modelmentioning
confidence: 99%
“…Besides the fire-retardant coatings and waterproof coatings, there are many other functional coatings, such as heat insulation coatings [111][112][113][114], self-healing coatings [115,116], sterilization coatings [117], icephobic coatings [118], and anticorrosive coatings [119], which are also indispensable in construction engineering.…”
Section: Othersmentioning
confidence: 99%